Effect of applied weather data sets on the computational assessment of hygrothermal performance of historical masonry - Kočí, Jan; Černý, Robert (International Conference “Environmental Engineering”, 2017)
Several historical wall assemblies together with several weather data sets are investigated in order to study the effect of environmental load on hygrothermal performance of historical buildings. The effect of weather data is assessed using several damage functions with the emphasis placed on frost induced damage. The climatic data are represented by six different weather data sets, namely by the test reference year, positive and critical weather years, together with the meteorological data measured by the autors during the time period of 2013–2015. Special attention is paid to the recent weather data as there is an apparent trend of average temperature increase in the Central Europe in last few years. The results presented in the paper confirm the warming trend which is manifested by virtually no frost induced damage observed for weather years 2014 and 2015 in the analyzed historical building envelopes.
Keywords: climatic data; historical buildings; sandstone; damage function; temperature